Open access musicology : Volume two - Epstein, Louis K.; Barolsky, Daniel (2022)
Open Access Musicology (OAM) publishes peer-reviewed, scholarly essays primarily intended to serve students and teachers of music history, ethno/musicology, and music studies. The constantly evolving collection ensures that recent research and scholarship inspires classroom practice. OAM essays provide diverse and methodologically transparent models for student research, and introduce different modes of inquiry to inspire classroom discussion and varied assignments. Addressing a range of histories, methods, voices, and sounds, OAM embraces changes and tensions in the field to help students understand music scholarship. Volume 2 of OAM expands the disciplinary, topical, and geographical ranges of our endeavor, with essays that rely on ethnographic and music theoretical methods as well as historical ones. The essays in this volume touch on music from Europe, South America, and Asia, spanning the 16th century to the present. Throughout, the contributing authors situate music in political, religious, racial, economic, and other cultural and disciplinary contexts. This volume therefore expands what scholars generally mean when they refer to "musicology" and "music," always with an eye toward relevance and accessibility...